Archives of Physiotherapy - Barbero, Marco; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Archives of Physiotherapy will cease to be published by BMC as of 31st December 2023. The journal is continuing in cooperation with a new publisher, AboutScience, from 1st January 2024. To submit your manuscript to Archives of Physiotherapy, you can visit the new submission system at AboutScience. Please contact the Editor-in-Chief for information regarding the new publisher and any submissions in progress. BMC will continue to host an archive of all articles previously published in the journal and all articles published in Archives of Physiotherapy during its time with BMC will remain fully searchable via the BMC website. Archives of Physiotherapy (formerly Italian Journal of Physiotherapy) is an open access journal disseminating research covering all aspects of physiotherapy. Featured topics include clinical trials in different areas of disability (musculoskeletal, neurological, cardio-pulmonary), diagnostic, measurement-focused, observational, prognostic and qualitative studies, as well as systematic reviews, meta-analyses and case reports. The journal also welcomes Letters to the Editor, which provide thoughtful debate on issues of concern to the physiotherapy profession and related disciplines. Publication costs for manuscripts meeting specific criteria will be covered by the journal partner. Please contact the journal editor for further information.
Keywords: Physical therapy; Clinical psychology; Rehabilitation; Mentally ill$1 (BRehabilitation.s; Chiropractic; Physiotherapy; Rehabilitation Psychology; Chiropractic Medicine